ANALISIS PENERAPAN METODE TIME AND MATERIAL PRICING DALAM MENENTUKAN HARGA JUAL JASA SERVIS DAN SUKU CADANG PADA CV. CASTROL BIKE POINT DIAN MOTOR PALEMBANG - Hendra Musa; Khairani Ulya Fitri (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2021)
This research was knowing how to apply the time and material pricing method in determining the selling price of service and spare parts at Castrol Bike Point Dian Motor Palembang. The scope of research on determining the selling price of service and spare parts at Castrol Bike Point Dian Motor Palembang. This research uses primary data and secondary data, interviews and observations, uses library research and field studies through interviews and documentation. The analysis technique use the comparative analysis, comparing the determination of the selling price and spare parts that have been carried out by Castrol Bike Point Dian Motor Palembang. The variables: time and material pricing method as the independent variable (variable X) and the selling price as the dependent variable (variable Y). The results, CV. Castrol Bike Point Dian Motor Palembang has not / does not use the time and material pricing method, only based on the completion time of service work, so that it affects the selling price and affects the decrease in profits. CV. Castrol Bike Point Dian Motor Palembang has not detailed the selling price of time and the selling price of materials, the selling price of service and spare parts is charged to consumers.